The service quality of sales representative from PERTAM Properties in selling the properties / Khurzaimah Daud - Daud, Khurzaimah (Faculty of Business and Management, 2009)
This study takes part of the service quality of the PERTAM Properties Sdn Bhd during in year 2007. The gap analysis is to find what factors that contributes towards improvement sales performance in the company based on the service quality provided by sales representative. Based on the, A sale is the pinnacle activity involved in selling products or services in return for money or other compensation. It is an act of completion of a commercial activity. The "deal is closed", means the customer has consented to the proposed product or service by making full or partial payment (as in case of installments) to the seller. A sale is completed by the seller, the owner of the goods. It starts with consent (or agreement) to an acquisition or appropriation or request followed by the passing of title (property or ownership) in the item and the application and due settlement of a price, the obligation for which arises due to the seller's requirement to pass ownership, being a price the seller is happy to part with ownership of or any claim upon the item. The purchaser, though a party to the sale, does not execute the sale, only the seller does that. To be precise the sale completes prior to the payment and gives rise to the obligation of payment. If the seller completes the first two above stages (consent and passing ownership) of the sale prior to settlement of the price the sale is still valid and gives rise to an obligation to pay.